Single cell analysis reveals satellite cell heterogeneity for proinflammatory chemokine expression - Andre, Alexander B.; Rees, Katherina P.; O’Connor, Samantha; Severson, Grant W.; Newbern, Jason M.; Wilson-Rawls, Jeanne; Plaisier, Christopher L.; Rawls, Alan (Frontiers in Cell and Developmental Biology, 2023)
The expression of proinflammatory signals at the site of muscle injury are essential for efficient tissue repair and their dysregulation can lead to inflammatory myopathies. Macrophages, neutrophils, and fibroadipogenic progenitor cells residing in the muscle are significant sources of proinflammatory cytokines and chemokines. In these studies, we examined the contribution of satellite cells, the stem cell population of skeletal muscle, to proinflammatory signaling. Mouse satellite cells in culture are able to express Tnfa, Ccl2, and Il6, within 2 hours of lipopolysaccharide treatment. Single cell RNA sequencing revealed the satellite cell cultures consisted of seven clusters representing the continuum between activation and differentiation. Lipopolysaccharide treatment led to a heterogeneous pattern of induction of C-C and C-X-C chemokines (e.g., Ccl2, Ccl5, and Cxcl0) and cytokines (e.g., Tgfb1, Bmp2, Il18 and Il33) associated with innate immune cell recruitment and satellite cell proliferation. One cell cluster was enriched for the antiviral interferon pathway under control conditions and induced by lipopolysaccharide treatment to express Ccl5, Cxcl10, Bmp2, I118, and Il33. Activation of the antiviral interferon pathway in satellite cells was also detectable at the site of cardiotoxin induced muscle injury. These data demonstrate that satellite cells respond to inflammatory signals and secrete chemokines and cytokines. Further, we identified a previously unrecognized subset of satellite cells that may act as sensors for muscle infection or injury.